Photochemical Degradation of Imazethapyr Herbicide in Aqueous Media - Debbab, Mohamed; Barkani, Hasna; Habib El Azzouzi, El; Tai, Fadwa; Mountacer, Hafida; Zrineh, Abdallah; El Hourch, Abderrahim; El Ghazali, Abdelkader; El Azzouzi, Mohammed (Asian Journal of Chemistry, 2012)
The photodegradation process of imazethapyr (IMZT) has been investigated under simulated sunlight using HPK lamp in aqueous media. In order to examine the effect of pH, we irradiated the solution at pH 2.7, 3.5, 4, 5.7 and 9. The photodégradation of imazethapyr appears to be more effective when pH > pKa and in the absence of oxygen. The major photodégradation products formed mainly by a photohydrolyze process and Norrish II reaction.